Mystery Box Transactions in the Perspective of Fiqh Muamalah: A Validity Analysis Based on Gharar and Maysir Principles - Hasan, Faradila; Niu, Fitria Ayu Lestari; Sumanta, Muhammad Julianto (Al-'Aqdu: Journal of Islamic Economics Law, 2025)
This study aims to analyze the validity of mystery box transactions from the perspective of fiqh muamalah (Islamic commercial jurisprudence) with a focus on the principles of gharar (uncertainty) and maysir (gambling). This qualitative research employs a literature review approach of 32 scientific articles (2001-2025) and is supported by interview data with mystery box consumers. Data analysis uses content analysis and thematic analysis techniques, organized into six discussion themes. Mystery box transactions do not meet the validity requirements of Islamic sale contracts as they contain elements of gharar (excessive uncertainty) due to unclear transaction objects and maysir (speculation) resembling gambling. This practice violates the principle of bayan (clarity), which is an essential requirement in contracts, and contradicts the concept of interadhin (mutual consent) in QS. An-Nisa verse 29. Although consumers are aware of the incompatibility of this practice with Sharia, entertainment motivation drives them to continue engaging in transactions. The absence of khiyar (inspection option) rights and potential seller exploitation further reinforce the fasid (invalid) status of these transactions. Conventional mystery box models are not Sharia-compliant and require fundamental modifications toward better transparency. Collaboration among consumers, business practitioners, regulators, scholars, and e-commerce platforms is needed to develop an alternative "halal mystery experience" that remains innovative yet compliant with muamalah principles, along with massive education on Sharia-based digital transactions for Muslim communities.